1980
DOI: 10.3758/bf03197614
|View full text |Cite
|
Sign up to set email alerts
|

Interactive presentation in multitrial free recall

Abstract: This paper explores whether free recall performance and organization can be facilitated using computer-controlled interactive presentation, where stimulus presentation on Trial N+1 depends on the individual subject's prior recall history. A series of experiments investigated the effects of two types of response-contingent presentation order manipulations and of selective tagging manipulation designed to highlight the presentation of previously nonrecalled items. An initial experiment using 20-word lists showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…New measures of free recall, based on Friendly and Franklin's (1980) multiple-trial free-recall experiments, are included here. The percentage of times that subjects recalled these words on the first three trials and the number of subjects involved in each estimate are reported .…”
Section: Multiple-trial Free Recallmentioning
confidence: 99%
See 2 more Smart Citations
“…New measures of free recall, based on Friendly and Franklin's (1980) multiple-trial free-recall experiments, are included here. The percentage of times that subjects recalled these words on the first three trials and the number of subjects involved in each estimate are reported .…”
Section: Multiple-trial Free Recallmentioning
confidence: 99%
“…Experiments 1-5 have the same basic design as that described in Friendly and Franklin (1980), and differed only in the number of words and number of trials of !earning. The design for these studies was a 2 x 3 factorial with the six independent groups representing a two-Ievel "tagging" manipulation combined with three presentation orders.…”
Section: Multiple-trial Free Recallmentioning
confidence: 99%
See 1 more Smart Citation